2014
DOI: 10.1038/bjc.2014.531
|View full text |Cite
|
Sign up to set email alerts
|

Tumour responses following a steroid switch from prednisone to dexamethasone in castration-resistant prostate cancer patients progressing on abiraterone

Abstract: Background:Abiraterone is a CYP17A1 inhibitor that improves survival in castration-resistant prostate cancer (CRPC). Abiraterone is licensed in combination with prednisone 5 mg twice daily to prevent a syndrome of secondary mineralocorticoid excess. We hypothesised that a ‘steroid switch' from prednisone to dexamethasone would induce secondary responses in patients progressing on abiraterone and prednisone 5 mg b.i.d.Methods:We performed a ‘steroid switch' in patients with CRPC at PSA progression on abirateron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 12 publications
4
49
0
2
Order By: Relevance
“…In these patients abiraterone was continued and prednisone was switched to 0.5-1 mg dexamethasone/d. There were responses demonstrated by PSA as well as by imaging [77,78]. The level of evidence for this intervention is low.…”
Section: Treatments and Schedules For Mcrpcmentioning
confidence: 88%
“…In these patients abiraterone was continued and prednisone was switched to 0.5-1 mg dexamethasone/d. There were responses demonstrated by PSA as well as by imaging [77,78]. The level of evidence for this intervention is low.…”
Section: Treatments and Schedules For Mcrpcmentioning
confidence: 88%
“…In an early study of abiraterone treated without concomitant steroids, the addition of dexamethasone on progression was capable of inducing PSA responses [18]. Recently, the change from prednisolone to dexamethasone in patients progressing on abiraterone showed PSA declines and RECIST responses after switching steroids [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PSA response rates, defined as a 50% or more reduction in PSA levels associated with dexamethasone and prednisolone were reported to be 47% and 24% (P = 0.05), respectively, in CRPC patients during a randomized Phase II trial [67]. Based on this, a hypothesis that a "steroid switch" from prednisone to dexamethasone would be effective in the treatment of CRPC patients with disease progression under abiraterone and prednisone treatment has been suggested [72]. In fact, one retrospective study of 30 CRPC patients who underwent such a "steroid switch" while abiraterone was administered, showed that durable PSA responses occurred in up to 40% of the patients [72].…”
Section: Combination With Next-generation Antiandrogensmentioning
confidence: 99%